Ranibizumab versus bevacizumab for ophthalmic diseases related to neovascularisation: a meta-analysis of randomised controlled trials. - Bin Wu; Haixiang Wu; Xiaoyan Liu; Houwen Lin; Jin Li (PLoS ONE)
Background Bevacizumab is believed to be as effective and safe as ranibizumab for ophthalmic diseases; however, its magnitude of effectiveness and safety profile remain controversial. Thus, a meta-analysis and systematic review appears necessary. Methods PubMed and EMBASE were systematically searched with no restrictions. All relevant citations comparing ranibizumab and bevacizumab were considered for inclusion. Pooled effect estimates were obtained using a fixed- and random-effects meta-analysis. Results Nine independent randomised-controlled clinical trials (RCTs) involving 2,289 participants were identified. Compared with bevacizumab, the overall combined weighted mean difference (WMD) of the mean change in visual acuity for ranibizumab was 0.52 letters (95% CI -0.11-1.14). The odds ratios (ORs) of gaining ≥15, gaining 5-14, losing 5-14 and losing ≤15 letters were 1.10 (95% CI 0.90-1.33), 0.93 (95% CI 0.77-1.11), 0.89 (95% CI 0.65-1.22) and 0.95 (95% CI 0.73-1.25), respectively. The risk of serious systemic events increased by 17% (95% CI 6%-27%, p = 0.0042) for bevacizumab treatment in comparison with ranibizumab. No statistically significant differences between the two treatments were found for the nonfatal arterial thrombotic events, ocular serious adverse, death from vascular and all causes events. Conclusions Bevacizumab is not inferior to ranibizumab as a treatment for achieving visual acuity. The use of bevacizumab was associated with an increased risk of developing serious systemic events. Weighing the costs and health outcomes is necessary when selecting between bevacizumab and ranibizumab for ophthalmic diseases. Due to the limitations of the available data, further research is needed.